2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6609844
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating between best performing features for seizure detection and data selection

Abstract: Abstract-Seizure detection algorithms have been developed to solve specific problems, such as seizure onset detection, occurrence detection, termination detection and data selection. It is thus inherent that each type of seizure detection algorithm would detect a different EEG characteristic (feature). However most feature comparison studies do not specify the seizure detection problem for which their respective features have been evaluated. This paper shows that the best features/algorithm bases are not the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Aside from temporal spike statistics (rate, regularity, etc. ), features reflecting amplitudes and signal energy (e. g. line-length), might be interesting since they are popular in seizure detection (Logesparan et al, 2013). Criteria (2) and (3), however, cannot be satisfied easily when using amplitudes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from temporal spike statistics (rate, regularity, etc. ), features reflecting amplitudes and signal energy (e. g. line-length), might be interesting since they are popular in seizure detection (Logesparan et al, 2013). Criteria (2) and (3), however, cannot be satisfied easily when using amplitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Existing spike detection algorithms therefore commonly focus on solitary spikes with high spike amplitudes or clearly discernible waveforms (Anjum et al, 2018; Chauvière et al, 2012; Huneau et al, 2013; Karoly et al, 2016; Krook-Magnuson et al, 2013). Seizure detectors, on the other hand, are mostly designed to specifically detect large, generalized seizures (Esteller et al, 2001; Gardner et al, 2006; Krook-Magnuson et al, 2013; Logesparan et al, 2013). These seizure detectors are often based on measures of signal energy, which can vary substantially depending on signal quality.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the spectral power in low frequencies (delta, theta, and alpha bands) constituted the most reliable signature of the state of consciousness, distinguishing between vegetative state (VS), minimally conscious state, and conscious state (CS). The spectral entropy in the 1 to 45 Hz frequency band showed higher values in minimally conscious and CS than in VS. Logesparan et al 18 analyzed the performance of 65 measures including 17 time domain, 12 Fourier transform, 4 continuous wavelet transform, and 32 discrete wavelet transform based measures, for online data selection and seizure occurrence detection. They concluded that discrete wavelet transform–based power in the 0 to 3.125, 3.125 to 6.25, 6.25 to 12.5, and 12.5 to 25 Hz frequency bands yielded a 0.97 value of the area under the curve in a receiver–operating characteristic analysis and were selected as the best discriminating features for seizure occurrence detection.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The continuous discharges of polymorphic waveforms of different amplitude and frequency can be captured using spectral and wavelet features. 1318 Apart from these, statistical measures 1719 and entropy measures 2023 have been proposed to characterize EEG time series. The brain symmetry index of spatial and temporal measures has been proposed to localize the hemisphere of seizure onset, 9,16 and an algorithm using autoregressive spectra has been designed for the detection of temporal lobe seizures.…”
mentioning
confidence: 99%
“…Manual analysis of this data for the identification of epileptic activities is extremely time consuming as the predominant state is the interictal (between seizure) period. Algorithms for detecting seizures have been developed, to reduce the analysis time and aid epileptologists by preselecting only the regions of interest in the EEG signals for review [4], [5], [6]. Such algorithms are known to have accuracy issues in patients with sporadic seizures where they are likely to miss detection of seizures or end up with large number of false positives, and can consequently lead to misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%